Predicational encoding in Upper Guinea linguistic area - Truppi, Chiara (Revista do GEL, 2021)
The paper aims to study nominal and locative predication in Upper Guinea Portuguese-related creoles and the West African languages, mentioned in the literature as substrate - Mandinka, Wolof, and Temne - and/or adstrate - several Atlantic languages. We will look at three features that characterize the copular systems of Upper Guinea creoles: (i) the split between nominal and locative predication, (ii) nonverbal predication, and (iii) copulaless predication. The comparison of our findings in the Upper Guinea creoles and in the languages that contributed to their formation and/or to their further development will allow us to assess influences of the latter in the emergence of the predicational system of this group of creoles. Further outputs will be to show, on the one hand, the grammatical proximity of Upper Guinea creoles as to their predicational system and, on the other hand, to uncover possible commonalities and differences among the Atlantic languages.